Characterization of Dunggilata Gold Tailings and Treatment Process Recommendations - Ninasafitri; Vivi Dia Afrianti Sangkota; Yayu Indriati Arifin (Postgraduate, University of Mataram, 2025)
Rare earth elements (REEs) are a group of seventeen metallic elements consisting of scandium (Sc), yttrium (Y), and fifteen other lanthanide elements. Rare earth metals have an important role in various technologies, so the analysis and separation of these elements from their minerals is very important to do. This study aims to characterize the tailings through X-Ray Diffraction (XRD), X-Ray Fluorescence (XRF), and Inductively Coupled Plasma Mass Spectrometry (ICP-MS) techniques. The results of XRD analysis show that the mineral composition of tailings is dominated by quartz (SiO₂) with a percentage of 88%, followed by albite (NaAlSi3O8) with a percentage of 11%. In addition, the results of XRF analysis show that the main elemental composition in the tailings consists of SiO₂ (69.294%), Al₂O₃ (20.20%), and Fe₂O₃ (4.681%). In addition, heavy metal concentrations in the tailings indicate a potentially serious risk of environmental pollution, with arsenic (As) reaching 100 ppm and mercury (Hg) more than 5 ppm. In addition, rare earth elements identified in the tailings include cerium (Ce) at 14,578 ppm, lanthanum (La) at 7,850 ppm, and neodymium (Nd) at 6,897 ppm. This method is expected to help tailings management, reduce environmental impacts, and support sustainable mineral utilization.